If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(-6u+3)-2u=4(u-2)-1
We move all terms to the left:
-4(-6u+3)-2u-(4(u-2)-1)=0
We add all the numbers together, and all the variables
-2u-4(-6u+3)-(4(u-2)-1)=0
We multiply parentheses
-2u+24u-(4(u-2)-1)-12=0
We calculate terms in parentheses: -(4(u-2)-1), so:We add all the numbers together, and all the variables
4(u-2)-1
We multiply parentheses
4u-8-1
We add all the numbers together, and all the variables
4u-9
Back to the equation:
-(4u-9)
22u-(4u-9)-12=0
We get rid of parentheses
22u-4u+9-12=0
We add all the numbers together, and all the variables
18u-3=0
We move all terms containing u to the left, all other terms to the right
18u=3
u=3/18
u=1/6
| B/7=a/4 | | C/7=a/4 | | 7y-14=5y-20 | | -5w-45=-9(w+1) | | 16y-10=4y | | F(x)=x+1/6 | | -4.1+4y=2.3 | | 11v=8v+21 | | X^2+2*x=870 | | -15x-24=12-24x | | -3y+8.9=4.1 | | X+10=-3x+3 | | 8.4=5u-4.1 | | 5.5=-7u+16.7 | | 16x+26+24x-146=20x+40 | | -20=1/2x | | -13.5+8y=12.1 | | 2x+9+49=90 | | x=R+R*x/x+R | | (5x+8)+(9x+12)=M | | u-9.4=6.72 | | 2x+x-4x=14 | | 36=1.5a-4a | | u+4=-3 | | 18x-17=+7x+137 | | x=-(-R)+√(-R)^2-4*1*(-R) | | 6m+15m=105 | | 7y^2-21y-280=0 | | y=450-(2)^30 | | 1/2(2y+4)-7=-1/8(16y-32) | | 2(2w)+2w=96 | | 56=2(2w-2)+2w |